Smart Grid: A Review: - (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The idea has been beaten around for years, but now the money and the will are converging to turn the old analog electric grid into the next big digital network. The smart grid starts its transformation from an overhyped and ill defined concept to a set of clearly articulated pieces and working prototypes. A Smart Grid is an electricity grid equipped with modern computer systems and communication networks. The primary goal of a Smart Grid is controlling the distribution of electricity as optimal as possible. All sides agree that today’s aging analog and mechanical electric grid needs to be dragged into the era of digital networks. The promises are compelling. Moving to a smarter electrical grid is imperative not only for the nation but also for the planet. However, we must be realistic about the risks and anticipate and mitigate the security and privacy problems they introduce in term of barrier. As this paper focus on barriers in Smart Grid and its possible solution.